The progressivity and regressivity of aid to the social sectors - Bob Baulch; Le Vi An Tam (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper analyses the distribution of total aid and aid to the social sectors between 2009 and 2011. Its key findings are four-fold. First, despite the stated objectives of donors, total aid disbursements are broadly neutral, favouring neither the most deprived nor relatively well-off countries. Second, the pattern of social sector aid disbursements follows those for total aid. Third, the aid allocation patterns of bilateral and multilateral donors differ, with multilateral donors generally being more focused on the poorest countries. Finally, the distribution of aid for health and population is more progressive than that for education or other social sectors.
Keywords: F35; I15; I25; Z18; 330; aid; social sectors; concentration curves; progressivity